Imaging Recommendations for Positron Emission Tomography (PET) in Oncology - Chaturvedi, Arvind K.; Mahajan, Abhishek; Sen, Saugata; Swamy, Shivakumar S.; Shah, Diva; Chakrabarty, Nivedita (Indian Journal of Medical and Paediatric Oncology, 2023)
Cancer is one of the leading causes of morbidity and mortality. Imaging studies are central to the initial staging and follow-up management of cancers. In the past, oncologists have largely relied on anatomical imaging for staging, restaging, and therapy monitoring. The introduction of positron emission tomography-computed tomography (PET-CT) and its availability has transformed the practice of cancer imaging. PET-CT is an imaging technique that provides complementary information to imaging by CT or magnetic resonance imaging alone as it incorporates functional imaging to the anatomic information. It actually embeds tumor biology on the anatomical image. There are significant contributions of the CT component in adding value to the strength of PET-CT. PET-CT is useful for initial staging of cancers. It is particularly useful in detection of distant metastases, in assessing response to therapy and in detection of recurrence. Its utility in restaging and follow-up of cancers is now well established. Its role varies across different primary cancer sites. To cover the role of PET-CT in all cancer types is neither the intention nor feasible in a single article. In this article, an attempt will be made to highlight the generic concepts of PET-CT imaging and its role in primary staging and post-therapy follow-up across some common malignancies. Its pitfalls and limitations will also be discussed.
Keywords: imaging; oncology; PET-CT